A New Expression for Higher Order Accelerations and Poles Under the One Parameter Planar Hyperbolic Homothetic Motions - Sahin, Serdal; Yuce, Salim (SPRINGER BASEL AG, 2016)
The one parameter planar hyperbolic homothetic motion was introduced in Ersoy and Akyigit (Adv Appl Clifford Algebras 21:297-313, 2011). We give a formula for higher order accelerations and poles under this motion. In the case of the homothetic rate h 1 we obtain the higher order accelerations and poles under one parameter planar hyperbolic motion which was given by Sahin and Yuce (Math Probl Eng 2014, 2014). Also, the higher order velocities and accelerations are analyzed by taking the angle of the rotation instead of the parameter of the motion.
Keywords: Hyperbolic numbers; Hyperbolic homothetic motion; Kinematics; Mathematics; Physics